2019
DOI: 10.24220/2318-0897v27n3a4014
|View full text |Cite
|
Sign up to set email alerts
|

Alterações farmacocinéticas de antimicrobianos em situações especiais: uma revisão narrativa

Abstract: Até o ano de 1940, as doenças infecciosas eram uma das principais causas de morte no Brasil. Atualmente, apesar de um grande declínio, a mortalidade ainda é elevada em relação a países desenvolvidos e a outros países da América Latina. Dessa maneira, o objetivo do presente trabalho foi relatar as alterações fi siológicas em condições específi cas, as consequências na farmacocinética dos antimicrobianos e ainda o impacto do ajuste de dose em tais situações. Realizou-se uma revisão narrativa de artigos publicado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 103 publications
0
3
0
5
Order By: Relevance
“…Studies of essential oils containing spathulenol as a major compound have reported some biological activities, such as antiproliferative, anti-inflammatory, and antimicrobial activities. And in this sense, do Nascimento et al (2018) investigated antiinflammatory, antiproliferative activity against MCF-7 and OVCAR-3 cell lines of essential oil extracted from Psidium guineense (Myrtaceae) leaves. The results indicated the presence of 80.7% spathulenol.…”
Section: Essential Oil Dexamethasonementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of essential oils containing spathulenol as a major compound have reported some biological activities, such as antiproliferative, anti-inflammatory, and antimicrobial activities. And in this sense, do Nascimento et al (2018) investigated antiinflammatory, antiproliferative activity against MCF-7 and OVCAR-3 cell lines of essential oil extracted from Psidium guineense (Myrtaceae) leaves. The results indicated the presence of 80.7% spathulenol.…”
Section: Essential Oil Dexamethasonementioning
confidence: 99%
“…Cigarette smoke contains several chemical constituents, including polycyclic aromatic hydrocarbons, which are mainly responsible for altering liver enzymes. The pathophysiological changes present in smoking can affect the absorption, distribution, metabolism, and excretion processes ( de Sousa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vários órgãos são capazes de metabolizar fármacos, mas essa função é exercida, principalmente, pelo fígado (SULAIMAN et al, 2022), é essencial conhecer quais alterações farmacocinéticas que estão ocorrendo para a determinação de esquemas posológicos adequados, assim aumentando a eficácia antimicrobiana e diminuindo seus efeitos adversos e tóxicos (SOUSA et al, 2018).…”
Section: Introductionunclassified
“…These agents have a high adaptive and transmutation capacity that is linked to their genomic structure, which gives them the exchange of genes between bacteria (EmyInumaru et al, 2019). Thus, bacteria began to promote infectious processes that were only discovered in the 19 th century when research related to these pathogens began (Sousa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%